2020
DOI: 10.1101/2020.12.01.406215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction and Analysis of Protein-Protein Interaction Network of Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a disease with multidimensional complexities. Many attempts have been made over the years to treat this disease but its incidence is rising. For this reason, the need to identify and study new candidate NAFLD biomarkers is of utmost importance. Systems-based approaches such as the analysis of protein-protein interaction (PPI) network could lead to the discovery of new disease biomarkers that can then be translated into clinical practice. The aim of this study is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 104 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…A previous study suggested that downregulation of GRB2 improved hepatic steatosis, glucose metabolism, oxidative stress, and apoptosis by modulating the insulin signaling pathway in HepG2 cells ( Shan et al, 2013 ). According to Amanatidou and Dedoussis (2021) , GRB2 is one of the candidate NAFLD-related proteins. TF is one of the major matrix protein of hen eggshell membranes that consists of 12 to 13% of total egg white protein ( Ko and Ahn, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that downregulation of GRB2 improved hepatic steatosis, glucose metabolism, oxidative stress, and apoptosis by modulating the insulin signaling pathway in HepG2 cells ( Shan et al, 2013 ). According to Amanatidou and Dedoussis (2021) , GRB2 is one of the candidate NAFLD-related proteins. TF is one of the major matrix protein of hen eggshell membranes that consists of 12 to 13% of total egg white protein ( Ko and Ahn, 2008 ).…”
Section: Discussionmentioning
confidence: 99%